The polyvariate specificity of personality psychological resources (Actual Problems of Psychology in Educational Institutions, 2021)
. The article is devoted to the problem of psychological resources,which is actively studied in modern foreign and domestic psychology. Theacute relevance of the importance of its research both for theory andpractice is emphasized. A theoretical review of some modern concepts ofpsychological resources is presented, different definitive positions regardingthe interpretation of the basic concept are considered. The psychologicalessence of resources in the context of activity, adaptation, socially mediatedand other scientific paradigms is revealed. The role of resources in thestructure of resistant behavior is emphasized. An attempt is made toidentify the polyvariate specificity of the phenomenon, which is mediatedby a complex of vital needs. Prospects for further research are outlined.
Keywords: psychological resources; individual capabilities; experience; potential; adaptation; self-realization; life creation; life fulfillment